Ablaut and neo-ablaut in Baltic and Indo-European - Petit, Daniel (Baltistica, 2017)
It is often assumed that PIE ablaut, used as a sub-morpheme accompanying other morphemes, tends to recede over time in the history of the individual Indo-European languages. On the other hand, it has been argued by some scholars that ablaut is often productive enough to expand over categories that did not have it originally. Both positions were advocated in the literature, the former by Mańczak (1958), the latter by Kuryłowicz (1947). In this paper, dedicated to Prof. Wojciech Smoczyński, this debate is discussed and illustrated by Baltic examples.